2019
DOI: 10.1177/0892705719838010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graphene oxide on the mechanical and thermal properties of graphene oxide/hytrel nanocomposites

Abstract: Polymer nanocomposites offer enhancement in thermomechanical and physicochemical properties of polymers with the presence of a little amount of nanostructured fillers such as carbon nanotubes, graphene, and layered silicates. A facile and rapid preparation of hytrel (HTL)-graphene oxide (GO) nanocomposites is done via a solution mixing method. The influence of GO content (0.1, 0.5, 1, 2, and 5 wt%) on mechanical and thermal properties of GO/HTL nanocomposites has been evaluated by using various techniques such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
2
25
0
1
Order By: Relevance
“…Improvements in the thermomechanical and physicochemical properties of hytrel-based nanocomposites filled with small amounts of nanostructured fillers such as carbon nanotubes, graphene, and layered silicates were also observed in Pandei et al [ 15 ].…”
Section: Introductionmentioning
confidence: 81%
“…Improvements in the thermomechanical and physicochemical properties of hytrel-based nanocomposites filled with small amounts of nanostructured fillers such as carbon nanotubes, graphene, and layered silicates were also observed in Pandei et al [ 15 ].…”
Section: Introductionmentioning
confidence: 81%
“…A second minor weight loss observed for all materials ranged from 120 to 180 • C due to desorption of vapors from the hardening agent [62]. In aprevious study, it was reported that GO begins to decompose/deteriorate at a variety of elevated temperatures of 120 • C [63], 150 • C [51] and 200 • C [20], which leads to the loss of its surface-bound oxygen functional groups. The TGA for GO composites did not have a significant weight loss compared to the pure epoxy, possibly due to the small GO loadings.…”
Section: Thermal Gravimetric Analysismentioning
confidence: 96%
“…As a result of GO's compatibility with polymers, GO has been added to various polymer matrix materials. Example polymers include polycarbonate [17], a biodegradable polyester, poly(ε-caprolactone) [18], unsaturated polyester resin [19], a polyester elastomer [20], poly (vinyl alcohol) [21], polybenzimidazole [22] and polypropylene [23].…”
Section: Introductionmentioning
confidence: 99%
“…Some common examples of synthetic polymers are polyethylene, polypropylene, polyethylene terephthalate etc. [44,46]. Fig.…”
Section: Synthetic Polymersmentioning
confidence: 98%